2020
DOI: 10.1088/1755-1315/518/1/012030
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian Organic Farmers: The Long Journey of Farmers’ Groups Towards Organic Farming Sustainability (A Case Study in Rukun Farmers Group, Yogyakarta)

Abstract: The Rukun farmer group is the first organic farmer group formed in the Yogyakarta region. The Rukun farmer group started organic cultivation through local varieties of rice cultivation in 2006 and received organic certification in 2011 and 2015. The Rukun farmer group became a representative farmer group as a sample in this study in order to identify the issues of organic farming. The challenge faced by organic farmer groups at the moment was the limited support of both funding and managerial parties. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Some previous studies showed a significant positive relationship between farmers' education and climate change adaptation [ 61 ], but some also showed a negative relationship [ 62 ]. Organic farmers have higher education, so as to absorb technological innovations including innovations to adapt to climate change [ 48 , 63 ]. Another factor influencing farmers' selection of adaptation strategies is experience.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies showed a significant positive relationship between farmers' education and climate change adaptation [ 61 ], but some also showed a negative relationship [ 62 ]. Organic farmers have higher education, so as to absorb technological innovations including innovations to adapt to climate change [ 48 , 63 ]. Another factor influencing farmers' selection of adaptation strategies is experience.…”
Section: Discussionmentioning
confidence: 99%
“…Another problem is that the livestock group does not function properly if there is no assistance from the government. Irham et al (2020) added that farmer groups in Indonesia are still very dependent on government funding to carry out organizational activities. Therefore, it is necessary to create a system that can support the independence of farmer groups.…”
Section: Discussionmentioning
confidence: 99%
“…The development of organic agriculture in a scattered pattern is also found in Sleman Regency, Special Region of Yogyakarta Province. A previous study (Irham et al, 2020) showed that, in Sleman Regency, organic farming was carried out in various farmer groups scattered in relatively small areas, thereby reducing farm efficiency and increasing the cost of certification for each organic farmer group. Therefore, the determination of zones or areas for organic farming needs to be realized to improve farming efficiency and ensure the sustainability of organic farming systems.…”
Section: Analytical Frameworkmentioning
confidence: 99%
“…A previous study by Irham et al (2020) showed that organic farming in Sleman Regency was carried out in various farmer groups scattered in relatively small areas, reducing farming efficiency and increasing certification costs for each organic farmer group. Therefore, the determination of organic farming areas needs to be realized to improve farming efficiency and ensure the sustainability of the organic farming system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation